1996
DOI: 10.1557/s1092578300002118
|View full text |Cite
|
Sign up to set email alerts
|

High-Power High-Temperature Heterobipolar TransistorWith Gallium Nitride Emitter

Abstract: A new heterobipolar transistor was made with the wide bandgap semicon-ductors gallium nitride (GaN) and silicon carbide (SiC). The heterojunction allows high injection efficiency, even at elevated temperatures. A record current gain of ten million was obtained at room temperature, decreasing to 100 at 535°C. An Arrhenius plot of current gain vs 1/T yields an activation energy of 0.43 eV that corresponds to the valence band barrier blocking the escape of holes from the base to the emitter. This activation energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…[1][2][3][4][5] The large direct band gap of 3.4 eV, high breakdown voltage with added advantage of high thermal conductivity, and thermal stability of GaN have led to electronic devices that can operate at high temperatures. 6 GaN has also received enormous attention due to its applications in white light sources. 7 Applications in spintronic devices for magnetic sensors, high-density memories, and spin polarized light emitters for optical encoding have been proposed, based on ferromagnetic doping of GaN.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The large direct band gap of 3.4 eV, high breakdown voltage with added advantage of high thermal conductivity, and thermal stability of GaN have led to electronic devices that can operate at high temperatures. 6 GaN has also received enormous attention due to its applications in white light sources. 7 Applications in spintronic devices for magnetic sensors, high-density memories, and spin polarized light emitters for optical encoding have been proposed, based on ferromagnetic doping of GaN.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] GaN-based bipolar junction transistors and heterojunction field effect transistors are another potential application field. 5,6 The need for both n-type and p-type dopants for the realization of practical structures has led to active research to find the most efficient atomic impurities. For wide-gap semiconductors like SiC and GaN, Si is used as shallow n dopant.…”
Section: Introductionmentioning
confidence: 99%
“…They estimated that GaN/AlGaN thyristors might support up to 5 kV operating voltages with current densities of 200 A/cm 2 and operate at frequencies exceeding 2 MHz. Pankove et al (1996) reported on a new Heterojunction Bipolar Transistor that used a heterojunction between GaN and SiC. The transistor exhibited an extremely high gain of ten million at room temperature, decreasing to 100 at 535°C.…”
Section: Gan Bipolar Transistorsmentioning
confidence: 99%